Peran Deiksis dalam Membentuk Respons Emosional dan Konflik Antar Mahasiswa di Kota Makassar - Joko Purwanto; Irham Rahman; Rusliana Rusliana (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to examine the role of deixis in shaping emotional responses and conflicts among university students in Makassar City. The background is grounded in recurring student clash incidents frequently triggered by communication misunderstandings and offense arising from negatively perceived language use. Deixis, as a linguistic element whose meaning depends on the context of utterance, is hypothesized to influence students’ emotional states and potentially trigger inter-student conflicts. The study employed a mixed methods approach with a sequential explanatory design. The first phase involved distributing questionnaires to 150 students from various universities in Makassar, while the second phase consisted of in-depth interviews with 18 informants and six weeks of field observation. The results show that deixis use is positively and significantly correlated with students’ emotional responses (r = 0.612; p < 0.05) and with the intensity of inter-student conflicts (r = 0.521; p < 0.05). Emotional response was confirmed as a partial mediator in the relationship between deixis and student conflict. Qualitatively, interview and observation findings confirm that exclusive deictic forms such as mereka (‘they’) and kalian (‘you all’) often reinforce social boundaries between groups and accelerate conflict escalation, whereas inclusive deixis such as kita (‘we’) tends to build solidarity and a conducive communicative atmosphere. This study concludes that deixis is a non-neutral psychosocial instrument: its use can shape social perceptions, trigger negative emotional responses, and heighten the potential for inter-student conflict, particularly in multicultural campus environments such as Makassar City. The implications of this study underscore the importance of enhancing deictic literacy and communicative awareness among students as a preventive measure against social conflict in higher education settings.